Modeling of PV system and parameter extraction based on experimental data: Review and investigation. (15th March 2020) - Humada, Ali M.; Darweesh, Salih Y.; Mohammed, Khalid G.; Kamil, Mohammed; Mohammed, Samen F.; Kasim, Naseer K.; Tahseen, Tahseen Ahmad; Awad, Omar I.; Mekhilef, Saad
Highlights: An accurate single-diode PV model developed based on the five PV parameters. PV parameters extraction technologies have been reviewed based on its accuracy. Results shown an excellent correspondence compared to legacy works. PV Parameters performance shown good convergence in both I–V and P–V curves. PV model validated with other two PV models and two real PV systems. Abstract: This paper presents a new approach to the extraction of a single-diode five-parameter model and its performance evaluation. The proposed model can analytically describe the current–voltage (I–V) and power–voltage (P–V) characteristics of a photovoltaic (PV) module in different conditions. The PV parameters mainly identify the accuracy of any PV model. Different evaluation criteria have been used in this study. All benchmark used to compare current results accuracy with literature studies outcomes. In addition, the performance of the five parameters tested. Results of PV parameters performance showed clear improvements, which are evident in the I–V and P–V characteristics. Consequently, the proposed model introduces five accurate and flexible parameters, compared to legacy work. The extracted parameters are based on nine coefficients. Results also show the effect of the five parameters on maximum power point (MPP), short circuit current ( Isc ), and open circuit voltage ( Voc ). Furthermore, a brief review on the PV parameter extraction methods and its accuracy level has been completed.